Podcast: Its Implementation for Informative Public Speaking Skill - Hanifah Zakiyyah Fatin; Finny Anita; Elly Syahadati; Rahayu Meliasari (IKIP PGRI Pontianak, 2023)
This research aimed to find how the implementation of podcast for informative public speaking skill and to find out the students responses toward the implementation of podcast in informative public speaking skill of English Education Study Program of IKIP PGRI Pontianak. This research used a case study approach. To obtain the data, the researcher used observation technique and direct commmunication technique, they were observation checklist and interview as tools of data collection. The subject of this research was the second semester students of IKIP PGRI Pontianak. To analyze the data, researcher used in this research was descriptive narrative. This technique is determined through three steps, Data Reduction, Data Display, and Conclussion (Miles and Huberman, 1984) from the results of observation checklist and interview.Implementing the podcast have advantages to students, one of them when the practice students of podcast can help improve students' english skills, especially in the speaking. The activities by video live podcast support the advantages of the implementation of podcast in public speaking course, and implementation of podcast in public speaking course is important to speak more fluently and comfortably, practice public speaking, train self-confidence, and can be useful for public speaking in the future, so students can get a more personal learning experience and confidence in doing public speaking. It could be the reason that using podcast to teach students how to speak English would improve their speaking skill.Keywords: Podcast, Public Speaking Skill, Informative, Second 2nd Semester.